Handling Constraints in Combinatorial Interaction Testing in the Presence of Multi Objective Particle Swarm and Multithreading - Ahmed, Bestoun S.; Gambardella, Luca M.; Afzal, Wasif; Kamal Z., Zamli (Elsevier Ltd, 2017)
Combinatorial testing strategies have lately received a lot of attention as a result of their diverse applications. In its simple form, a combinatorial strategy can reduce several input parameters (configurations) of a system into a small set based on their interaction (or combination). In practice, the input configurations of software systems are subjected to constraints, especially in case of highly configurable systems. To implement this feature within a strategy, many difficulties arise for construction. While there are many combinatorial interaction testing strategies nowadays, few of them support constraints.